2017
DOI: 10.1186/s13104-017-2550-8
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 genetic diversity and primary drug resistance mutations before large-scale access to antiretroviral therapy, Republic of Congo

Abstract: BackgroundIn this work, we investigated the genetic diversity of HIV-1 and the presence of mutations conferring antiretroviral drug resistance in 50 drug-naïve infected persons in the Republic of Congo (RoC). Samples were obtained before large-scale access to HAART in 2002 and 2004.MethodsTo assess the HIV-1 genetic recombination, the sequencing of the pol gene encoding a protease and partial reverse transcriptase was performed and analyzed with updated references, including newly characterized CRFs. The asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…10 The spread of CRF01_AE has been tracked from Thailand to Vietnam, China, and ultimately a global dissemination. [11][12][13][14] However, CRF01_AE has not extensively spread within Central Africa, with CRF01_AE infection having a prevalence of <1% in nearby Cameroon, 15 <4% in DRC, 16,17 <3% in Chad, 18,19 <1% in the Republic of the Congo, [20][21][22] and 6% in CAR 23 in recent studies. However, the extent to which CRF01_AE may still be circulating within recombinant strains cannot be evaluated with subgenomic sequences reported in most of these studies.…”
Section: Introductionmentioning
confidence: 99%
“…10 The spread of CRF01_AE has been tracked from Thailand to Vietnam, China, and ultimately a global dissemination. [11][12][13][14] However, CRF01_AE has not extensively spread within Central Africa, with CRF01_AE infection having a prevalence of <1% in nearby Cameroon, 15 <4% in DRC, 16,17 <3% in Chad, 18,19 <1% in the Republic of the Congo, [20][21][22] and 6% in CAR 23 in recent studies. However, the extent to which CRF01_AE may still be circulating within recombinant strains cannot be evaluated with subgenomic sequences reported in most of these studies.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, CRF02_AG is one of the most prevalent CRFs in the global HIV-1 epidemic, and is the major circulating recombinant form in West and Central Africa today [9,10]. According to previous studies, CRF02_AG was observed as the second most predominant genotype in the Republic of the Congo (URF, undetermined recombinant forms, was the most predominant) and the most prevalent genotype in Gabon, a neighboring country [2,11]. The distribution of genotypes in our study was almost identical to that found in Cameroon [12].…”
Section: Discussionmentioning
confidence: 99%
“…There are limited data available on the molecular characterization of HIV-1 in the RC. Studies performed in urban regions before the inclusion of DTG reported the predominance of specific circulating recombinant forms (CRFs), including CRF02_AG, and an important genetic variability with the accumulation of drug resistance mutations (DRM) [1,2]. This study aims to evaluate the drug resistance profile of HIV-1 within the pol region, and describe the circulating strains among ART-experienced patients in four semi-rural localities in the RC (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted in 44 selected antenatal clinics (ANCs) in 12 departments in RoC (five urban and seven rural) assessed 2979 pregnant women attending these facilities (Niama et al, 2017). The overall HIV infection rate was estimated to be 3.6%.…”
Section: Mother-to-child Hiv Transmissionmentioning
confidence: 99%